Integration of Islamic Values in STEAM Learning: Management Efforts to Realize Holistic Islamic Education - Hadi, Nur (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
STEAM (Science, Technology, Engineering, Arts, and Mathematics) learning based on Islamic values is an innovative approach in education that aims to form students who are intellectually capable and spiritually whole. This research is a qualitative study with a descriptive approach that aims to identify the needs of STEAM learning in Islamic schools and analyze the integration of Islamic values in the process. The research was conducted at SMA Adh-Dhuhaa Sukoharjo as one of the Islamic educational institutions that shows commitment to implementing the STEAM approach based on Islamic values Data obtained through interviews with school principals, subject teachers (Science, Mathematics, Technology, and Arts), curriculum coordinators, education staff, and students who are directly involved in the learning process, observation of learning activities, as well as documentation of curriculum and teaching tools. The data collection method used triangulation techniques, while the data analysis was carried out thematically with the Miles and Huberman interactive model. The results of the study show that there are six main needs in the implementation of Islamic STEAM, namely flexible curriculum, teacher collaboration, supporting facilities, innovative learning resources, value-based approaches, and teacher training. It is evident that STEAM learning with the integration of Islamic values is able to encourage a holistic education that combines mastery of science and the formation of spiritual character, and is worthy of being developed more widely in Islamic schools.